Constructing Social Attitudes and Religious Tolerance in Emerald Diversity through te Teaching of Religion and Cultural Values - Arifin, Ilfiana Firzaq; Musaddad, Akmad Arif; Sudiyanto, Sudiyanto (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
Diversity is already common place in Indonesia as a country that is nicknamed as the Emerald diversity. Indonesian state menghiasai diversity is seen as something that is very unique, but foreigners do not know that it is actually in it churned a result of lack of tolerance. SMK Nurul Ulum is a school that is not wished for it to happen. Therefore, this school creates an attitude of tolerance among human beings, which is based on the teachings of Islam, Christianity, Hindu-Buddhist and cultural values Pendhalungan. The method used in this article is using qualitative descriptive analysis techniques and observation. Descriptive analysis is done by reviewing a wide range of journals, books, articles and other sources that support. While the observation conducted at SMK Nurul Ulum Jember namely by conducting in-depth interviews to the relevant school. The results showed that with the use of the teachings of tolerance of various religious and cultural values Pendhalungan and use a good strategy, tolerance can be built effectively in this school.